On the similar spectral manifestations of protonic and hydridic hydrogen bonds despite their different origin - Maximilián Lamanec; Svatopluk Civiš; Pavel Hobza (Communications Chemistry)
Abstract Previously studied complexes with protonic and hydridic hydrogen bonds exhibit significant similarities. The present study provides a detailed investigation of the structure, stabilization, electronic properties, and spectral characteristics of protonic and hydridic hydrogen bonds using low-temperature infrared (IR) spectroscopy and computational methods. Complexes of pentafluorobenzene with ammonia (C₆F₅H⋯NH₃) and triethylgermane with trifluoroiodomethane (Et₃GeH⋯ICF₃) were analyzed using both experimental and computational tools. Additionally, 30 complexes with protonic hydrogen bonds and 30 complexes with hydridic hydrogen bonds were studied computationally. Our findings reveal that, despite the opposite atomic charges on the hydrogens in these hydrogen bonds, and consequently the opposite directions of electron transfer in protonic and hydridic hydrogen bonds, their spectral manifestations - specifically, the red shifts in the X–H stretching frequency and the increase in intensity - are remarkably similar. The study also discusses the limitations of the current IUPAC definition of hydrogen bonding in covering both types of H-bonds and suggests a way to overcome these limitations.